High Efficient Module of Boost Converter in PV Module - S.Daison KumarStallon; K.Vinoth Kumar; S.Suresh Kumar (Institute of Advanced Engineering and Science, 2012)
Within the photovoltaic (PV) power-generation market, the PV module has shown obvious growth. However, a high voltage gain converter is essential for the module’s grid connection through a dc–ac inverter. This paper proposes a converter that employs a floating active switch to isolate energy from the PV panel when the ac module is OFF; this particular design protects installers and users from electrical hazards. Without extreme duty ratios and the numerous turns-ratios of a coupled inductor, this converter achieves a high step-up voltage-conversion ratio; the leakage inductor energy of the coupled inductor is efficiently recycled to the load. These features explain the module’s high-efficiency performance. The detailed operating principles and steady-state analyses of continuous, discontinuous, and boundary conduction modes are described. A 15V input voltage, 200V output voltage, and 100W output power prototype circuit of the proposed converter has been implemented; its maximum efficiency is up to 95.3% and full-load efficiency is 92.3%.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1586